Inoculation with a psychrotrophic-thermophilic complex microbial agent accelerates onset and promotes maturity of dairy manure-rice straw composting under cold climate conditions. (November 2017) - Gou, Changlong; Wang, Yuqiong; Zhang, Xiqing; Lou, Yujie; Gao, Yunhang
Highlights: PTCMA was comprised of PBC and TCFC. PBC inoculation accelerated the rises in temperature at the onset of composting. TCFC inoculation significantly improved compost maturity. Composting of inoculating PTCMA is an efficient strategy in cold climates. Abstract: The objective was to determine the effects of psychrotrophic-thermophilic complex microbial agent (PTCMA) comprised of a psychrotrophic bacterium consortium (PBC) and a thermophilic cellulolytic fungi consortium (TCFC), on composting in a cold climate. Mixtures of dairy manure and rice straw were inoculated with PTCMA, PBC, TCFC and sterile water (control) and composted at an initial ambient temperatures of −2 to 5 °C. In compost piles inoculated with PBC or PTCMA, temperatures reached the thermophilic phase (>55 °C) faster (8–11 d) than piles inoculated with TCFC or control. Furthermore, compost inoculated with TCFC or PTCMA had greater decreases in total organic carbon and carbon-to-nitrogen ratios, as well as significant increases in total nitrogen, degradation of cellulose and lignin and germination index than PBC inoculation or Control compost. Consequently, inoculation with both (i.e. PTCMA) accelerated the onset and promoted maturity of composting under cold-climate conditions.